Dorsal Brain Stem Syndrome: MR Imaging Location of Brain Stem Tegmental Lesions in Neonates with Oral Motor Dysfunction - Quattrocchi, C.C.; Longo, D.; Delfino, L.N.; Cilio, M.R.; Piersigilli, F.; Capua, M.D.; Seganti, G.; Danhaive, O.; Fariello, G. (American Journal of Neuroradiology, 2010)
SUMMARY: The anatomic extent of brain stem damage may provide information about clinical outcome and prognosis in children with hypoxic-ischemic encephalopathy and oral motor dysfunction. The aim of this study was to retrospectively characterize the location and extent of brain stem lesions in children with oral motor dysfunction. From January 2005 to August 2009, 43 infants hospitalized at our institution were included in the study because of a history of hypoxic-ischemic events. Of this group, 14 patients showed oral motor dysfunction and brain stem tegmental lesions detected at MR imaging. MR imaging showed hypoxic-ischemic lesions in supra- and infratentorial areas. Six of 14 patients revealed only infratentorial lesions. Focal symmetric lesions of the tegmental brain stem were always present. The lesions appeared hyperintense on T2-weighted images and hypointense on IR images. We found a strong association (P < .0001) between oral motor dysfunction and infratentorial lesions on MR imaging. Oral motor dysfunction was associated with brain stem tegmental lesions in posthypoxic-ischemic infants. The MR imaging examination should be directed to the brain stem, especially when a condition of prolonged gavage feeding is necessary in infants. APGARappearance, pulse, grimace, activity, respirationCIconfidence intervalIRinversion recoverySEspin-echo